Edith Stein: the philosopher who finds to God - Cruz Acuña, Edgar (2013)
The purpose of this paper is to stand out the qualities of a Catholic intellectual who came to embrace the faith after a long journey of relentless pursuit of truth, which looked with reverence and devoted to their service. Edith’s personality, her spirit deliver, coherence and responsibility, is the exact example for all contemporary Christian intellectual sincerely seeking the truth, not only by the natural use of reason, but also of the light coming from above Christian faith. Her testimony of wisdom, faith, courage and commitment, church transcends boundaries, radiating conscientiously seeking Truth, Beauty, Justice and Happiness.